STUDY OF THE INFLUENCE OF SOLUTIONS OF MINERAL ACIDS, AMMONIA AND ALKALIS ON THE STRENGTH CHARACTERISTICS OF SPECIAL TEXTILE MATERIALS - MIHAILOVA, NINA; PRIVALA, VALERII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The issue of protecting workers in chemical industries is extremely relevant, since this industry is associated with high risks to human health and life. Contact with toxic substances and dangerous chemical reactions can lead to serious illness, disability or even death. Ensuring an adequate level of safety in the workplace, including the use of protective equipment and compliance with safety standards, is critical to preserving the health and life of workers. The protection of workers in chemical industries is even more important in the context of environmental safety and sustainable development. The introduction of modern technologies and innovations in production processes can significantly reduce the risks associated with chemical accidents and environmental pollution. In addition, the creation and maintenance of safe working conditions are important elements of the effective management of enterprises in the chemical industry. After all, protecting workers is not only a social responsibility, but also an important factor in improving productivity and competitiveness of production. The purpose of these studies is to improve the methodology for conducting studies of the effect of solutions of mineral acids and alkalis on samples of special materials that are provided for the manufacture of protective suits for workers in chemical industries. The authors of the publication propose for consideration the results of studies of the stability of special textile materials for the manufacture of protective clothing against the effects of chemical aggressive substances in the conditions of domestic chemical enterprises. The studies were carried out according to an improved methodology, which involves the use of an experimental KІM-1 installation. According to the criterion for determining the stability of materials in relation to the influence of chemical reagents, the value of the breaking load force of experimental samples was chosen.
Keywords: insulating protective suit; chemical industry; research methodology; chemically aggressive environment